Oral health of the elderly with Alzheimer's disease - Ribeiro, Giselle Rodrigues; Costa, José Luiz Riani [UNESP]; Bovi Ambrosano, Glaucia Maria; Rodrigues Garcia, Renata Cunha Matheus (Elsevier, 2012)
Objective: The objective of this study was to describe the oral health of elderly people diagnosed with Alzheimer's disease (AD). Study Design: Thirty elderly subjects with AD (mild, moderate, and severe) and 30 without AD (controls) were included in the study. Volunteer-reported oral health data were collected using the General Oral Health Assessment Index (GOHAI). Demographic and oral characteristics were assessed, including the number of natural teeth; number of decayed, missing, and filled teeth (DMTF); oral health index (OHI); removable prosthesis conditions; and oral pathologies. Results: GOHAI values were similar for both groups. Compared with the controls, the subjects with AD had a higher age, DMTF, OHI, and number of oral pathologies and a lower educational level and number of natural teeth. Conclusions: Elderly subjects with AD had poorer oral health than those without the disease. Despite the positive self-perception of their oral health, the oral health of subjects with AD tended to decline as their disease progressed. © 2012 Elsevier Inc.
Keywords: aged; Alzheimer disease; attitude to health; biofilm; comparative study; complete denture; cross-sectional study; dentition; denture; educational status; female; geriatric assessment; health; health survey; human; income; male; mouth disease; mouth hygiene; removable partial denture; self concept; stomatitis; tooth calculus; tooth disease; tooth occlusion; tooth plaque; Aged; Alzheimer Disease; Attitude to Health; Biofilms; Cross-Sectional Studies; Dental Calculus; Dental Occlusion; Dental Plaque; Dentition; Denture Retention; Denture, Complete; Denture, Partial, Removable; DMF Index; Educational Status; Female; Geriatric Assessment; Humans; Income; Male; Mouth Diseases; Oral Health; Oral Hygiene Index; Self Concept; Stomatitis, Denture; Tooth Diseases